ANALISIS FAKTOR PEMEROLEHAN BAHASA KEDUA ANAK USIA 6 TAHUN DENGAN RIWAYAT SPEECH DELAY TERHADAP KEMAMPUAN BERBAHASA INDONESIA - Apriyanti Nurliyah; H. Yusak Hudiyono (Bajang Institute, 2024)
Language is a period in which a particular language is applied or widely used by society to speak or communicate. Language comes from things we can hear and see, which have an impact on the way people speak, in this case the communication process. A formal atmosphere, which is created through planning and an informal atmosphere, which is created naturally. In the process of acquiring a second language, a formal atmosphere is very important, especially in the process of second language acquisition and success over the period of the second language acquisition process. This study further investigates the factors that influence the process of second language acquisition in children who have a history of delayed speech, as well as their native language skills. This study aims to compare bilingual abilities with Indonesian language abilities in six year old children. The aim of this research is to reach conclusions about the ability factor. Language is a particular place and situation where language is widely used by society to speak or communicate. Consists of everything that can be heard and seen, which has an impact on the way people speak, in this case the communication process. A formal atmosphere, which is created through planning and an informal atmosphere, which is created naturally. In the process of acquiring a second language, the formal atmosphere is very important, especially in the series of events of second language acquisition and the successful acceleration of second language acquisition. This study investigates the factors that influence the process of second language acquisition in children who have a history of delayed speech as well as their native language skills. This study used descriptive qualitative method. This research shows that the acquisition of a second language in children with a history of speech delays greatly influences the use of their mother tongue.